Areca nut - an unusual cause of small intestinal obstruction (Indian Journal of Case Reports, 2018)
Ingested foreign bodies are commonly encountered in clinical practice, especially in children. Till now, no case has been reported in the literature where a small intestinal obstruction was produced as a result of foreign body (areca nut) ingestion. We report a case of a 30-year-old female clinically presented as an acute intestinal obstruction of 4 days duration. Her plain X-ray abdomen showed multiple small intestinal fluid levels. Abdominal ultrasound showed dilated loops of small intestine. Contrast-enhanced computed tomography abdomen showed an intraluminal non-enhancing lesion near ileocecal junction. Exploratory laparotomy revealed 3 cm